2009
DOI: 10.1111/j.1365-2966.2008.14254.x
|View full text |Cite
|
Sign up to set email alerts
|

Red giant stellar collisions in the Galactic Centre

Abstract: We show that collisions with stellar--mass black holes can partially explain the absence of bright giant stars in the Galactic Centre, first noted by Genzel et al, 1996. We show that the missing objects are low--mass giants and AGB stars in the range 1-3 M$_{\odot}$. Using detailed stellar evolution calculations, we find that to prevent these objects from evolving to become visible in the depleted K bands, we require that they suffer collisions on the red giant branch, and we calculate the fractional envelope … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
97
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 81 publications
(97 citation statements)
references
References 49 publications
(149 reference statements)
0
97
0
Order By: Relevance
“…Mostly, collisions between stars or between stars and stellar remnants have been considered (e.g. Dale et al 2009), but recently it has been suggested that collisions between giants and dense clumps of gas in a star forming disk around Sgr A* could have stripped the giants and thus rendered them too dim to be observable with current technology (Amaro-Seoane & Chen 2014). Scenario (1b) has been shown to be a plausible result of the combination of star formation and dynamical evolution of the NSC.…”
Section: Does the Mwnsc Possess A Stellar Cusp?mentioning
confidence: 99%
“…Mostly, collisions between stars or between stars and stellar remnants have been considered (e.g. Dale et al 2009), but recently it has been suggested that collisions between giants and dense clumps of gas in a star forming disk around Sgr A* could have stripped the giants and thus rendered them too dim to be observable with current technology (Amaro-Seoane & Chen 2014). Scenario (1b) has been shown to be a plausible result of the combination of star formation and dynamical evolution of the NSC.…”
Section: Does the Mwnsc Possess A Stellar Cusp?mentioning
confidence: 99%
“…Further inside, the number density of the old -and therefore probably dynamically relaxed -stars is too flat to be consistent with the cusp scenario (Buchholz et al 2009). This observation could be attributed to a number of reasons, like a very long relaxation time (Merritt 2010) or the effect of stellar collisions on giant stars (Dale et al 2009). The presence (or not) of a stellar cusp at the GC must be considered ongoing research.…”
Section: Properties Of the Nuclear Star Clustermentioning
confidence: 99%
“…Similar results from MonteCarlo calculations were found by Freitag et al (2006) However, observations of red-giants in the Galactic center suggest a core-like structure in the inner regions of the GC (γ in the range 0 − 0.5; Do et al 2009;Bartko et al 2010;Genzel et al 2010. Nevertheless, it is not yet clear whether the distribution of red-giants reflect the overall distribution of stars in the GC, and various models had been suggested to explain both a "real" core distribution (Merritt 2010) or an apparent one (i.e., only reflecting the distribution of red-giants; Dale et al 2009;Amaro-Seoane & Chen 2014;Aharon & Perets 2015).…”
Section: Cusp and Core Models For The Nuclear Clustermentioning
confidence: 99%